Cost-effectiveness and budget impact of adding tranexamic acid for management of post-partum hemorrhage in the Indian public health system - Beena Nitin Joshi; Siddesh Sitaram Shetty; Kusum Venkobrao Moray; Himanshu Chaurasia; Oshima Sachin (BMC, 2023)
Abstract Background Postpartum hemorrhage (PPH) is the global leading cause of maternal mortality, affecting nearly 3 to 6 percent of all women giving birth in India. The World Health Organization (WHO) has updated its guidelines to recommend the early use of intravenous (IV) tranexamic acid (TXA) in addition to standard care for all diagnosed PPH cases. This study aimed to assess the cost-effectiveness of introducing TXA for PPH management in the Indian public health system. Methods A decision analytic model was built using a decision tree to determine the cost-effectiveness of administering IV TXA to women experiencing PPH within 3 h of birth to existing management with uterotonics and supportive care. Using a disaggregated societal perspective, the costs and consequences for a hypothetical cohort of women experiencing PPH in public health facilities was estimated. The model was populated using probabilities, clinical parameters, and utilities from published literature, while cost parameters were largely derived from a primary economic costing study. The primary outcome of interest was the incremental cost-utility ratio (ICUR). Associated clinical events and net benefits were estimated. One-way and probabilistic sensitivity analysis (PSA) was undertaken. The budget impact was estimated for a national-level introduction. Results For an estimated annual cohort of 510,915 PPH cases in India, the addition of IV TXA would result in a per-patient disaggregated societal cost of INR 6607 (USD 95.15) with a discounted gain of 20.25 QALYs, as compared to a cost of INR 6486 (USD 93.41) with a discounted gain of 20.17 QALYs with standard care PPH management. At an ICUR value of INR 1470 per QALY gained (USD 21), the addition of IV TXA is cost-effective in Indian public health settings. The intervention is likely to prevent 389 maternal deaths, 177 surgeries, and 128 ICU admissions per 100,000 PPH cases. The findings are robust under uncertainty, with 94.5% of PSA simulations remaining cost-effective. A cumulative increase of 2.3% financial allocation for PPH management over five years will be incurred for TXA introduction. Conclusions Addition of tranexamic acid for primary PPH management, as recommended by WHO, is cost-effective in Indian public health settings. Policy guidelines, training manuals, and facility checklists should be updated to reflect this recommendation.